Designing and Modeling of a Point Absorber Wave Energy Converter with Hydraulic Power Take-off Unit - Engin, Celalettin Dogukan; Yesildirek, Aydin (IEEE, 2015)
In this project, the primary aim is to produce optimum parameters for electric power generation via renewable sea wave energy for the Turkish sea coastlines. The modular system is composed of wave actuation mechanism, hydraulic system and generator. This system is used to model and compute the optimal parameters but also monitor the Turkish coastline characteristics. A hydrodynamic model based optimum PTO drives the generator that are further connected to other similar units to construct a wave energy farm. A test bench is created to mimic the operation of wave actuation in lab environment. This unit drives hydraulic system that can generate mechanical power to excite a generator shaft. Optimal wave actuation mechanism parameters suitable to our coastlines have been calculated. With these aims, the system designed on the basis of the mechanism that based on point absorber buoy. Initial design and hydrodynamic simulations in MATLAB/Simulink is given.
Keywords: wave energy; renewable; Turkish coastlines; offshore; point absorber; hydraulic energy converter; Energy & Fuels; Engineering